Growth and competitiveness of biotypes of crabgrass resistant and susceptible to acetyl coenzyme A carboxylase inhibiting herbicides - Ovejero, Ramiro Fernando López; Novo, Maria do Carmo de Salvo Soares; Carvalho, Saul Jorge Pinto de; Nicolai, Marcelo; Christoffoleti, Pedro Jacob (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to compare the growth and the competitive ability of two crabgrass (Digitaria ciliaris) biotypes, one resistant (R) and other susceptible (S) to the acetyl coenzyme A carboxylase inhibiting herbicides. Biotypes growth was determined by collecting the plant dry mass at 14, 21, 25, 28, 34, 42, 49, 57, 65, 72, 78, 86, 101, 111, and 118 days after emergence (DAE). Data of dry mass were adjusted to a logistic model, and were also used to calculate the absolute growth rate. Five experiments were installed to evaluate the intraspecific and interspecific competitive ability, using the substitutive method. The biotypes R and S were compared between themselves and each one of them with the soybean crop seeded in the same day or seven days after the seeding of the weeds. Plant proportions between species or biotypes used were: 5:0; 4:1; 3:2; 2:3; 1:4, and 0:5. The biotypes presented similar dry mass accumulation, absolute growth rate and interspecific competition, and the reduction of soybean mass was similar in the presence of R and S crabgrass biotypes, which suggests that R and S crabgrass biotypes have the same ecological adaptability.